A new species of the genus Hermanella Needham & Murphy (Ephemeroptera: Leptophlebiidae) from Northeastern Brazil - Almeida, Everlin; Costa, Sabrina; Mariano, Rodolfo (Zootaxa, 2016)
Hermanella angeli sp. nov. (Holotype male deposited in MZUSP: Itacaré municipality, Cachoeira Bom Sossego, 14°20’05.2”S, 39°01’27.4”W, 31.VII.2012, Mariano, R, Almeida, E & Costa, S. leg.) is described based on imagos and nymphs from the State of Bahia, Brazil. The new species can be distinguished by the following combination of characteristics, in male imagos: (1) costal and subcostal area of forewing brown (Fig. 5b); (2) thorax and abdominal terga predominantly brown (Fig. 2–3); (3) penes divided in apical 1/8 (Fig. 8); (4) penis lobe with ventral, long, curved spine (Fig. 7); (5) prosternum narrow (Fig. 1). In nymphs: (1) tarsal claws with 2–3 accessory denticles (Fig. 19); (2) mandible without setae near basal articulation (Fig. 13a); (3) prostheca of left mandible with spines on inner margin (Fig. 13b); (4) plate-like gills terminated in a finger-like process (Fig. 11).